2022
DOI: 10.1002/stc.3084
|View full text |Cite
|
Sign up to set email alerts
|

Development and performance evaluation of a robust suboptimal H ‐based proportional–integral controller–observer system with target tracking for better control of seismic responses

Abstract: In this article, a new full-and reduced-order proportional-integral (PI) controller is developed such that the target-tracking or commandfollowing problems become generic for a wide range of frequency inputs. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The efficacy of the proposed strategy was numerically validated for a TMD that is installed in Taipei 101 tower to alleviate the wind induced vibrations. Recently, Panda et al [4]; Zand et al [5] has demonstrated the application of integrated base-isolation and active control system (hybrid adaptive system) for both near and far-fault earthquakes, wherein a new full and reduced order proportional-integral 𝐻 ∞ controller is used to acuate the control device. Furthermore, the problem of designing a multi-sensor acceleration -strainbased output controller for hybrid adaptive systems has been discussed in Adarsh et al [6].…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of the proposed strategy was numerically validated for a TMD that is installed in Taipei 101 tower to alleviate the wind induced vibrations. Recently, Panda et al [4]; Zand et al [5] has demonstrated the application of integrated base-isolation and active control system (hybrid adaptive system) for both near and far-fault earthquakes, wherein a new full and reduced order proportional-integral 𝐻 ∞ controller is used to acuate the control device. Furthermore, the problem of designing a multi-sensor acceleration -strainbased output controller for hybrid adaptive systems has been discussed in Adarsh et al [6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of utmost importance to restrict excessively large bearing displacements in the baseisolated structures. In that context, various researchers have suggested multiple passive and semi-active control strategies to reduce the large bearing displacements of base-isolated structures with the help of supplemental dampers [26][27][28]30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature findings reveal increasing interest in the application of adaptive intelligent controllers in civil structures and smart control systems designed to cope with natural hazards. Panda et al [31] developed a robust H 1 -based servo-mechanism controller for better control of seismic responses by taking target tracking problems into account. Their findings show that the developed adaptive controller has a significant potential for reducing interstory drift in both SDOF and MDOF systems.…”
Section: Introductionmentioning
confidence: 99%